PREDICTING THE PINCHOUT DISTANCE OF SHORELINE TONGUES - Loseth T.M.; Helland-Hansen W. (My University, 2001)
Sand-rich shoreline tongues are common features of the stratigraphic record, and many of them are important petroleum reservoirs. The basinward extent of such shallow-marine deposits is highly variable, from a few to a few hundred kilometres. Although indirect information exists, the question as to what parameters actually cause this variation and their relative importance has not been addressed. Here, it is argued that the sand pinchout distance of regressive-to-transgressive shoreline tongues is controlled by (1) the type of depositional system (e.g. fluvial-, tide- or wave-dominated); (2) the regressive and transgressive shoreline trajectories; and (3) the depth of transgressive erosion. In contrast to the shoreline trajectory, the angle of turnaround, defined by the pathway taken by the regressive and subsequent transgressive shorelines, is simple to measure and gives a first approximation of the pinchout distance. For otherwise equal systems, the pinchout distance is inversely related to the angle of turnaround.